Calendar Month Effect in Bursa Malaysia: A Comparison between Shariah-Compliant Portfolio and Non-Shariah- Compliant Portfolio - Rohuma, Hani Nuri; Brijlal, Pradeep (International Journal of Economics and Financial Issues, 2023)
This research examines whether the return of the Shariah-compliant portfolio (SCP) relative to the non-Shariah-compliant portfolio (NSCP) is subject to any calendar month effect on Bursa Malaysia over 12 years. The non-Shariah-compliant stocks were selected rather than conventional stocks to ensure that all stocks were completely independent since the Shariah-compliant stocks are part of the conventional stocks. A new portfolio (SCP–NSCP) that represented the monthly difference return between the SCP and NSCP was constructed, and by employing the robust standard errors regression, the results indicated that, after applying the Capital Asset Pricing Model (CAPM) with dummy variables, only in June, the return of SCP significantly outperform the return of NSCP. However, the existence of this calendar month anomalies between the SCP and NSCP will raise questions about the efficiency of Bursa Malaysia.